The Influence Of Customer Service On Customer Satisfaction At Bank Jabar Banten (BJB) Syariah, Sumedang Branch Office - Tresnawati, Siti; Ramadhan, Putri Leony Nur; Solihin, Budi (Pascasarjana Universitas Pasundan, 2024)
This study aims to analyze the significance of the influence of customer service on customer satisfaction at BJB Syariah KCP Sumedang. Customer service is an important part of the banking industry, especially in Islamic banking, where customer satisfaction is the main indicator of operational success. The selection of this topic is driven by the increasing competition in the Islamic banking sector, which requires banks to not only ensure that customers receive quality service. This study uses a quantitative method with a survey approach. Primary data were collected through questionnaires distributed to 100 customers of BJB Syariah KCP Sumedang, and analyzed using a simple linear regression technique to identify the extent to which customer service quality variables affect customer satisfaction. The results analyzed show that customer service quality has a significant and positive influence on customer satisfaction. The better the quality of service provided, the higher the level of satisfaction felt by customers. The conclusion of this study emphasizes the importance of continuous improvement and enhancement in customer service quality as an effective strategy to increase customer satisfaction. The recommendation of this study is the need for regular training for customer service officers to maintain and improve service quality.